Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Kinerja Pelaku Bisnis Onlineshop - Anggreany Hustia; Nadia Nadia; Ratu Anugrah (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
The aim of this research was to find the effects of internal and external factor to the performance of online shop entrepreneur. The population was Education Product Consultant at PT. Tigaraksa.Tbk that got the Reward Trip to Singapore – Malaysia 2019. Purposive sampling was the method of of this research. The sample will be choose based on the entrepreneur who sale their product through media online. This research used primary data from questioner that calculate by using SPSS. The techniques for analysis the data used multiple linear regression, simultaneous test (F test), partial test (t test) and determination test. The result of simultaneous and partial tests showed that there were impacts between internal and external factor to the performance of online shop entrepreneur in onlineshop.